The Role of Culture Consumption in an Increase of Deception Marketing , a Sample Survey of Cosmetic Users Employees College of Administration & Economics / University of Mosul - خليل, ليلى جار الله (Journal of Economics and Administrative Sciences, 2019)
Economics / University of Mosul AbstractThe spread of the phenomenon of excessive buying in our society, especially for cosmetics, and at the same time increase the marketing deception by the organizations to take quick profit 'and accordingly was identified the problem of research in several questions, including:Is there a significant effect of consumption culture on marketing deception?                                                                                             The importance of the current research is that it deals with two important topics' culture of consumption has become a reality and marketing deception is constantly increasing and to study goals, including recognition of the extent of awareness of the subjects of the research variables' Based on the problem of research has been formulated several hypotheses of which there is no significant effect of the culture of consumption in marketing deception  .                     A sample of 40 employees was selected and the questionnaire was adopted for data acquisition. Several statistical methods were used to analyze the data and extract the results using the spss program. The research concluded that there was a significant correlation between consumption culture and marketing deception. According to researchers .